National parks of Ecuador and its promotion through Social Networks [Parques Nacionales de Ecuador y su promoción en las Redes Sociales] - Armijos Maurad, A. (2016)
The government of Ecuador there has managed a model of development that it values to all his cultures, his idiosyncrasy and his natural environments, beside managing, across the National System of Protected Areas (SNAP), to implement actions in benefit of the conservation of the natural resources since it has happened in the National Parks. Likewise, other relevant progresses that have to be considered in all this studding, it is the development of the Social Networks, as contribution to the promotion of the knowledge of the National Parks, by means of his labor in the communication of the above mentioned resources. The aim principal of this investigation is based in analyzing the promotion in Facebook of four National Parks of Ecuador. The purpose is to determine if really they take advantage of the above mentioned channel as generator of contents, visibility and interactivity and manage therefore, to make profitable the opportunities that nowadays offer the technologies. © 2016 AISTI.